2015
DOI: 10.1111/bph.13133
|View full text |Cite
|
Sign up to set email alerts
|

A metabolite of Danshen formulae attenuates cardiac fibrosis induced by isoprenaline, via a NOX2/ROS/p38 pathway

Abstract: BACKGROUND AND PURPOSECardiac fibrosis is a common feature of advanced coronary heart disease and is characteristic of heart disease. However, currently available drugs against cardiac fibrosis are still very limited. Here, we have assessed the role of isopropyl 3-(3,4-dihydroxyphenyl)-2-hydroxylpropanoate (IDHP), a new metabolite of Danshen Dripping Pills, in cardiac fibrosis mediated by the β-adrenoceptor agonist, isoprenaline, and its underlying mechanisms. EXPERIMENTAL APPROACHIdentification of IDHP was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…Unlike other adrenergic agents such as isoproterenol (a nonselective b-AR agonist) (Yin et al 2015), pharmacological stimulation of b 2 -AR with CB induces hypertrophy of TA (fast-twitch), masseter muscle (fast-twitch), and cardiac muscle, but not SOL (slow-twitch) in WT, without causing an increase in interstitial collagen (fibrosis) as shown in this study (Fig. 2) and previously by other groups (Wong et al 1997(Wong et al , 1998Zeman et al 2000), even though mice with a very high level of overexpression of b 2 -AR develop fibrosis (Liggett et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other adrenergic agents such as isoproterenol (a nonselective b-AR agonist) (Yin et al 2015), pharmacological stimulation of b 2 -AR with CB induces hypertrophy of TA (fast-twitch), masseter muscle (fast-twitch), and cardiac muscle, but not SOL (slow-twitch) in WT, without causing an increase in interstitial collagen (fibrosis) as shown in this study (Fig. 2) and previously by other groups (Wong et al 1997(Wong et al , 1998Zeman et al 2000), even though mice with a very high level of overexpression of b 2 -AR develop fibrosis (Liggett et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A novel compound, isopropyl 3‐(3,4‐dihydroxyphenyl)‐2‐hydroxypropanoate (IDHP), was found to be a bioactive metabolite of Danshen during the research process of CDDP metabolism in vivo (Pei et al ., ; Wang et al ., 2011a; Zheng et al ., ). Our previous pharmacological study showed that IDHP possesses a variety of biological activities such as anti‐myocardial and anti‐cerebral ischemia (Cheng et al ., ; Tian et al ., ), anti‐hypoxia (Xiong et al ., ), anti‐arrhythmic (Wang et al ., ), anti‐myocardial fibrosis (Lu et al ., ; Yin et al ., ), anti‐oxidant (Cheng et al ., 2011), anti‐inflammation (Wang et al ., ) and vasodilative effects (Li et al ., ; Wang et al ., ). These remarkable activities give IDHP the potential to become a promising new drug for fighting diseases in the cardio‐cerebrovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacologically active ingredients of a phytocomplex such as TCM compound formulations ( fufang ) are not always the original natural molecules but may be their host‐specific metabolites or molecular complexes formed following co‐administration of selected herbs. We have previously discovered an active Dantonic metabolite (isopropyl 3‐(3,4‐dihydroxyphenyl)‐2‐hydroxy‐propanoate, IDHP) and found it was a NO‐independent vasodilator, which attenuated cardiac fibrosis in rats as well (Zheng, Zhao, Zhao, et al, ; Yin et al, ). Tanshinol (DSS, (+) β‐(3,4‐dihydroxyphenyl) lactic acid) is the primary ingredient in an aqueous extract of S. miltiorrhiza and exhibits pleiotropic activities, such as protection of vascular endothelial cells against homocysteine (Hcy)‐induced damage (Chan et al, ) and protection of myocardium from ischaemia/reperfusion injury (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%